Application of DRBEM for evaluating buckling problems of perforated thin plates - Purbolaksono J.; Aliabadi M.H. (EuroJournals, Inc., 2023)
This paper presents buckling analysis of the perforated thin plates by the dual reciprocity boundary element method (DRBEM). The plate buckling equations of the method are presented as a standard eigenvalue problem. Simply supported rectangular plates with different locations of a circular hole subjected to compressive loads are evaluated. Effects of a circular hole located at some distance away from the central of plate on the corresponding critical compressive load coefficients are evaluated. The finite element method (FEM) results are also presented for comparison. EuroJournals Publishing, Inc. 2009.